A Comparative Analysis of Arm Regeneration in Astropecten indicus and Ophiocnemis marmorata - Bazeer, Asbar Banu; Sekar, Divya; Nagarajan, Prithiviraj; Rangarajalu, Kumar; Sivanandham, Mohan (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Echinoderms are renowned for their exceptional regenerative abilities, but interspecies comparisons have lacked rigorous quantitative analysis. This study compares arm regeneration in Astropecten indicus and Ophiocnemis marmorata under controlled conditions (37±0.7 ppt salinity, 17±0.3°C). Following 1 cm arm amputations (n=10/species), O. marmorata formed blastemas in 48–72 h, significantly faster than A. indicus (72–120 h, P<0.01). By week 5, 90% of O. marmorata had regrown arms to 2.0±0.2 cm, while only 55% of A. indicus achieved 1.8–2.0±0.3 cm by week 6. O. marmorata developed tube feet by week 2, compared to week 3 in A. indicus, and regained full mobility by week 4, while A. indicus required 5–6 weeks. Scarring was minimal in O. marmorata (<5%), compared to 15% in A. indicus. The survival rate of O. marmorata was higher (80%) compared to A. indicus (60%). These findings reveal distinct regenerative strategies: O. marmorata regenerates rapidly and without scarring, while A. indicus shows slower, fibrotic healing. The superior performance of O. marmorata, including faster blastema formation and complete anatomical restoration, makes it an ideal model for anti-fibrotic research, stem cell studies, and scaffold-free tissue engineering. This study provides the first quantitative framework for comparing echinoderm regeneration, offering promising insights into potential applications for human regenerative medicine.